ASSISTING LYN'Z HEALTH & BEAUTY CARE FOR TRADEMARK REGISTRATION AS AN EFFORT TO PROVIDE INTELLECTUAL PROPERTY RIGHTS - Cindy Anggelia; Hari Sutra Disemadi (Universitas Internasional Batam, 2022)
Law Number 20 of 2016 concerning Marks and Geographical Indications in Article 1 Paragraph 1 explains that a mark is a sign that can be displayed graphically in the form of images, logos, names, words, letters, numbers, color arrangements, in 2 (two) dimensions. , sound, hologram, or a combination of two or more of these elements to distinguish goods and/or services produced by persons or legal entities in the activities of trading goods and/or Services. Lyn'z Health & Beauty Care is a business engaged in health and beauty services. The reason for the owner of the brand is notregistering the